Enhancing the lipid productivity of yeasts with trace concentrations of iron nanoparticles - Pádrová, Karolína; Čejková, Alena; Cajthaml, Tomáš; Kolouchová, Irena; Vítová, Milada; Sigler, Karel; Řezanka, Tomáš (Folia microbiologica, 2016)
Oxidative stress induced by zero-valent iron nanoparticles (nZVIs) was used to improve lipid accumulation in various oleaginous and non-oleginous yeasts-Candida sp., Kluyveromyces polysporus, Rhodotorula glutinis, Saccharomyces cerevisiae, Torulospora delbrueckii, Trichosporon cutaneum, and Yarrowia lipolytica. The highest lipid yields occurred at 9-13 mg/L nZVIs. Gas chromatography-mass spectrometry was used for the quantitative and qualitative analysis of the fatty acids. It showed an increasing abundance of polyunsaturated fatty acids, especially essential linoleic acid, in the presence of nZVIs. Our results suggest that nZVIs can be used to improve not only lipid production by oleaginous microorganisms but also the nutritional value of biosynthesized unsaturated fatty acids.
Keywords: cytosol; železo; kvasinky; Oxidative Stress; metabolismus lipidů; Yeasts; Nanoparticles; oxidační stres; mastné kyseliny; plynová chromatografie s hmotnostně spektrometrickou detekcí; Gas Chromatography-Mass Spectrometry; Iron; Cytosol; Lipid Metabolism; Fatty Acids; nanočástice